(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
Sustainability and health are two of the global challenges recognized by UN. Electronics is the pillar that supports the innovation in these sectors. However, current electronic components are non-biodegradable and release toxins in environment, while the implanted electronics is not compatible with soft human tissues. The aim of my research is to overcome these challenges through i) development of novel electronic material library, and ii) next-generation devices with new form factors. Through green chemistry we have developed novel biodegradable, biocompatible and bioresorbable electronic materials. Printed electronics is the new emerging fabrication technique that allows electronic components, circuits and devices to be put on a desired surface using nanoparticle inks. The synthesized materials are converted into printable inks to fabricate soft and flexible devices. I will showcase some of the case studies on the application of the materials and flexible devices.